Avaliação do consumo e da despesa de energia elétrica no estudo de concepção de sistema de abastecimento de água - FERREIRA, Jorge Fernando Hungria (Universidade Federal do Pará, 2019)
The definition of the Water Supply Systems (WSS) design is an important stage in the municipalities planning, since it has a direct impact in the implementation, operation and maintenance costs, and, as a consequence, in the economic sustainability of water supply companies. Thus, in the present research were studied alternatives of WSS design to the urban area Castanhal, considering the values of electricity energy consumption and operational cost in the period 2017-2037. The research was divided in three stages, being in the first characterized the Castanhal WSS (that uses underground water). After that, two alternatives of WSS design with raw water abstraction were analyzed and dimensioned. In the third stage, simulation was performed in the EPANET 2.0 Software to compare the consumption and cost of electric energy in the operational routines of WSS design alternatives. In the research, 14 WSS’s were identified in the Castanhal urban area, with capture in 46 shallow wells and 13 deep wells and with water treatment and reservation problems, attending only 28.36% of the urban population and 47.86% of loss index in distribution water. The WSS design alternatives were with superficial abstraction of raw water, one from Guamá river and another from Inhangapi river; with treatment and distribution of 64,293 m³/d to attend 270,935 inhabitants in 2037; and with operational routine to minimize pumping at peak time. After the dimensioning of WSS units and the simulations in the EPANET 2.0 software, 21,600,000 data were systematized, being 10,972,800 of water flow, 9,676,800 of manometric height and 950,400 of water level. With the results of the 2017 simulation, it was verified that the CE and DE values of the Guamá WSSs (0.53 kWh/m³ and 0.29 R$/m³) and Inhangapi (0.48 kWh/m³ and 0.26 R$/m³) were lower than the Actual WSS values (0.83 kWh/m³ and 0.35 R$/m³). In the results of the 2037 simulations of electricity consumption and cost, the best hydroenergetic performance of Inhangapi WSS (988,280 kWh/month and R$ 2.816.629,91/month) was verified in comparison with Guamá WSS (1,108,260 kWh/month and R$ 3.144.285,08/month), consuming at peak time 0.91% (10,112 kWh/month) in Guamá WSS and 1.01% (9,959 kWh/month) in Inhangapi WSS of total electricity consumption. Considering the present value of the accumulated electric energy cost in the project horizon, Inhangapi WSS (R$ 98.987.348,36) had savings of R$ 10.419.463,93 (9.52%) in relation to Guamá WSS (R$ 109.406.812,29), reason for the Inhangapi WSS to be defined as the best design alternative to universalization of water supply in the urban area of Castanhal in the period from 2017 to 2037.